The Concept of Wasatiyyah in The Views of al-Zamakhshari and Fakhr al-Dīn al-Rāzī - Tumin Tumin; Firman Mansir; Halim Purnomo (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
Bombings in the name of Islam, such as in Turkey, Indonesia, and the French have damaged the integrity of Islam. These acts of extremism are ubiquitous and lead to Islamophobia especially in western countries. While in fact, Islam has taught and promoted the concept of moderation (wasatiyyah) since its emergence in order to avoid extremism among humankind. One of the main underpinning verses in the Qur’an that talks about the concept of wasatiyyah is Surah Al-Baqarah, Verse 143. This paper explores two different views of theological schools, namely Al-Zamakhshari, who represents the Mu‘tazilites and Fakhr al-Dīn al-Rāzī, who represents the Ash’arites in dealing with the verse and its interpretations. In its analysis, the paper applied a theological approach to analyze the primary materials. It is expected that the findings will help in the implementation of the concept of moderation (Wasatiyyah) in the contemporary era. Finally, it will also serve as a guide on the ideal way of practicing Islam in order to eliminate and reduce extremism and foster peaceful co-existence between Muslims and adherents of other religions in the world.Pemboman atas nama Islam, seperti di Turki, Indonesia, dan Prancis telah merusak integritas Islam. Tindakan ekstremisme ini ada di mana-mana dan mengarah ke Islamofobia terutama di negara-negara barat. Padahal sebenarnya, Islam telah mengajarkan dan mempromosikan konsep moderasi (wasatiyyah) sejak kemunculannya untuk menghindari ekstremisme di antara umat manusia. Salah satu ayat utama yang mendasari dalam Al-Qur'an yang berbicara tentang konsep wasatiyyah adalah Surah Al-Baqarah, Ayat 143. Makalah ini mengeksplorasi dua pandangan yang berbeda dari sekolah-sekolah teologis, yaitu Al-Zamakhshari, yang mewakili Mu'tazilah dan Fakhr al-Dīn al-Rāzī, yang mewakili kaum Ash'ari dalam kaitannya dengan ayat dan interpretasinya. Dalam analisisnya, makalah ini menerapkan pendekatan teologis untuk menganalisis bahan-bahan primer. Diharapkan temuan ini akan membantu dalam penerapan konsep moderasi (wasatiyyah) di era kontemporer. Akhirnya, itu juga akan berfungsi sebagai panduan tentang cara ideal mempraktikkan Islam untuk menghilangkan dan mengurangi ekstrimisme dan menumbuhkan ko-eksistensi damai antara Muslim dan penganut agama lain di dunia.